IMPROVING NETWORK-BASED CALENDAR SCHEDULING IN CONSTRUCTION WORK PLANNING - Abdurakhmanov Ulugbek Arabdjon ogli; Rasuljon Khamitov Khasanjon ogli (Western European Studies, 2025)
In this article, the significance of network-based scheduling in the planning of contemporary construction works is examined, methods for improving such schedules are analyzed, and, based on the results obtained, recommendations are developed for their widescale practical application in accordance with construction norms and regulations, along with several specific proposals
Keywords: Construction; Gantt charts; linear schedules